2016
DOI: 10.1002/cncr.30330
|View full text |Cite
|
Sign up to set email alerts
|

Testing and referral patterns in the years surrounding the US Preventive Services Task Force recommendation against prostate‐specific antigen screening

Abstract: In the years surrounding the USPSTF recommendation, PSA behavior did not change significantly. Patients were referred at progressively higher average PSA levels. The implications for prostate cancer outcomes from these trends warrant further research into provider variables associated with actual PSA utilization. Cancer 2016;122:3785-3793. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
4
24
0
Order By: Relevance
“…Cohn et al reported on the practice patterns of a large Midwest health system and demonstrated an 11% decrease in PSA testing ordered by internal medicine and family practice physicians in the 6 months after the USPSTF guideline statement. Although Hutchinson et al observed negligible changes in PSA testing rates among primary care providers in a Southwest health system, their finding of increased PSAs at the time of urology referral supports our hypothesis of primary care retention of positive PSA screens. US population‐based survey and cancer registry data similarly support decreased PSA screening and decreased diagnoses of early prostate cancer .…”
Section: Discussionsupporting
confidence: 84%
“…Cohn et al reported on the practice patterns of a large Midwest health system and demonstrated an 11% decrease in PSA testing ordered by internal medicine and family practice physicians in the 6 months after the USPSTF guideline statement. Although Hutchinson et al observed negligible changes in PSA testing rates among primary care providers in a Southwest health system, their finding of increased PSAs at the time of urology referral supports our hypothesis of primary care retention of positive PSA screens. US population‐based survey and cancer registry data similarly support decreased PSA screening and decreased diagnoses of early prostate cancer .…”
Section: Discussionsupporting
confidence: 84%
“…found a 19% decrease in urologic referrals for elevated PSA 43 , and Hutchinson et al . found that although PSA testing rates did not change at their institution, PCPs were referring patients at increasingly higher PSA values, at an average of 2.56 ng/ml in 2012, 2.72 ng/mL in 2013, 3.06 ng/ml in 2014 and 3.84 ng/ml from 2015 onwards 39 . Dalela et al .…”
Section: Resultsmentioning
confidence: 99%
“…found that within their regional hospital network (2008–2012), 64.9% of PSA tests were ordered by internists and 23.7% by family physicians, while only 6.1% were ordered by urologists and 1.3% by hematologist/oncologists 17 . Several studies looked at differences in PSA test ordering among PCPs 21, 25, 26, 28, 31, 32, 39 . Using the National Ambulatory Medical Care Survey (NAMCS), Shoag et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have noted decreases in the rates of diagnosis of early stage disease . Disturbingly, early data suggest there may be an increase in high‐risk disease, but use associated with PSA, including subsequent referrals, urology visits, and treatments, may not have changed much . Although it is possible that this may be because of the more discriminate use of PSA screening among men who physicians believe are most likely to benefit from early detection, it is concerning that the current recommendations may result in decreased screening and diagnosis rates in higher‐risk men who are most likely to benefit from early detection and to require subsequent treatment.…”
mentioning
confidence: 99%